OPTIMASI FORMULA GEL EKSTRAK KAYU MANIS (CINNAMOMUM BURMANNII) : FRACTIONATION APPROACH - Siampa, Jainer Pasca; Lebang, Julianri Sari; Datu, Olvie Syenni; Khairuddin (Sam Ratulangi University, 2023)
Activities outside are unavoidable and lead to increased sun exposure to the skin. The purpose of this study was to formulate a gel using cinnamonraction as active ingredients. Cinnamon is extracted by maceration method using 70% ethanol then fractionated using n-hexane, ethyl acetate, and butanol solvents. The resulting fraction was then tested for total flavonoid content and antioxidant capacity using the DPPH method (2,2-diphenyl, 1-picrylhydrazil). Fractions that have strong antioxidant activity was further used as active ingredients. The test results of the total flavonoid content of n-hexane, ethyl acetate and butanol fractions were 0.265%w/wEQ; 1.035%w/wEQ; and 1.169%w/wEQ respectively. Testing of antioxidant capacity gave an IC50 value of 124.729ppm; 8.636ppm; and 7.858ppm. Furthermore, the butanol fraction was selected as the best fraction and used as the active ingredient of the gel formula. In conclusion, the butanol fraction could be formulated into a gel that met the requirements of physical characteristics.Keywords: butanol fraction, cinnamon, total flavonoid, antioxidant capacity, gel fraction